Isotropic and anisotropic components of the neutron emissions at the FN-II and PACO dense plasma focus devices - Castillo, F. (2003)
The average angular distribution of neutron emissions has been measured in the Fuego Nuevo II (FN-II) dense plasma focus device (5 kJ) by means of CR-39 plastic nuclear track detectors. When pure deuterium is used as the filling gas, the data can be adjusted to a Gaussian function, related to anisotropic emission, superposed on a constant pedestal, related to isotropic emission. When deuterium–argon admixtures are used, the anisotropic contribution is best represented by a parabola. The same analysis is applied to previously reported results, for fewer shots, in pure deuterium from the PACO device, which is similar in size to the FN-II. In both devices the anisotropic component is smaller than the isotropic one, but with different features. In PACO the anisotropic component is concentrated on a large narrow beam around the axis, but its contribution to the total neutron yield is significantly smaller than in the FN-II, where the anisotropic component spreads over a wider range. The neutron flux per shot is monitored in both devices with calibrated silver activation detectors, at 20˚ and at 90˚ from the axis. The average values of the neutron flux at these two angles are used, along with the angular distributions obtained form the track detectors, in order to estimate the absolute neutron yield of both the isotropic and the anisotropic contributions. From examining different groups of shots, it is found that the shape of the angular distribution is important in the estimation of anisotropy, and that the value usually reported, as the ratio of neutron counts head-on and side-on, as measured by activation counters, may be misleading.